Application of CAx technologies in modelling and simulation of CNC machine tool and processing complex part - Zoran, Pandilov; Gjorgji, Petrov (Editura Politehnica, 2021)
This research presents the use of CAx technologies in the design of a Computer Numerically Controlled machine. Тhe sub-assemblies and assemblies of the Computer Numerically Controlled machine are designed by using CAD (Computer Aided Design) software. Then the CNC machine virtual assembled model is presented. The model is loaded into other integrated CAD/CAM/CAE software and a NC code for a complex part (impeller) is generated. The next stage shows simulation of complex part (impeller) processing on a virtual Computer Numerically Controlled machine. By using CAE (Computer Aided Engineering) module of the integrated software, a static analysis of the loaded complex part (impeller) has been performed and its deformations and stress have been estimated for different materials and different rotation speeds. Based on the performed analyzes and simulations, a recommendation is given from which material the complex part (impeller) should be manufactured in order to meet the technical criteria and the costs for the used material and manufacturing to be as low as possible.
Keywords: Computer Aided Design (CAD), Computer Aided Manufacturing (CAM), Computer Aided Engineering (CAE), CAx technologies, CNC machine